2017
DOI: 10.3917/reof.150.0027
|View full text |Cite
|
Sign up to set email alerts
|

Mobilité entre générations et fluidité sociale en France

Abstract: À partir des enquêtes Formation – Qualification Professionnelle (INSEE) de 1970, 1977, 1985, 1993 et 2003, cet article analyse l’évolution de la mobilité sociale entre générations et de la fluidité sociale en France pour les hommes et femmes nés entre 1906 et 1973. Il établit que l’association statistique entre classe d’origine et classe de destination est plus faible dans les cohortes récentes que dans les cohortes anciennes, et montre aussi que la même association s’atténue avec l’avancée en âge, c’est-à-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
3
0
13
Order By: Relevance
“…To enable us to compare data within a consistent time frame, we adjust the survey data to the French System of National Accounts aggregates. This adjustment, which is similar to the adjustment carried out for the National Transfer Accounts (d 'Albis et al 2015;2017), ensures that the aggregate disposable income of individuals is equal to the National Accounts aggregates. Our sample is restricted to ordinary households residing in Metropolitan France.…”
Section: Disposable Income By Age and Cohortmentioning
confidence: 86%
See 1 more Smart Citation
“…To enable us to compare data within a consistent time frame, we adjust the survey data to the French System of National Accounts aggregates. This adjustment, which is similar to the adjustment carried out for the National Transfer Accounts (d 'Albis et al 2015;2017), ensures that the aggregate disposable income of individuals is equal to the National Accounts aggregates. Our sample is restricted to ordinary households residing in Metropolitan France.…”
Section: Disposable Income By Age and Cohortmentioning
confidence: 86%
“…Moreover, as those two studies used data from the same survey (Formation et Qualification Professionnelle), which does not contain explicit information on income, the authors had to estimate income. Using the same survey to study intergenerational mobility through social classes, Vallet (2017) concluded that mobility increased for the younger cohorts, and that improvements were larger for women than for men; while Ben-Halima et al (2014) showed that the degree of intergenerational persistence was less pronounced for daughters than for sons. The findings of both of these studies complement our results, which highlight the role of education in the reduction in intergenerational inequalities.…”
Section: Comparisons Of Incomes Across Cohortsmentioning
confidence: 99%
“…Lefranc (2018) shows that intergenerational persistence of men's income has increased since the cohorts born in the 1950s, and Alesina et al (2018) show that the French, like other Europeans, are pessimistic about intergenerational mobility. Concerning intergenerational mobility through social classes, Vallet (2017) concludes that mobility increased for younger cohorts and that the increase was larger for women than for men while Ben-Halima et al (2014) show that the intergenerational persistence was lower for daughter than for son.…”
Section: Discussionmentioning
confidence: 99%
“…Certaines barrières et grandes catégories de barrières présentes dans notre modèle théorique apparaissent en effet inexplorées dans les études empiriques mobilisées 23 (Ünver et al, 2018). Afin de réduire efficacement, dès leur origine, les inégalités éducatives et la faible mobilité sociale qui caractérisent la France, agir sur les inégalités d'accès aux modes d'accueil formels y est donc d'une importance cruciale (Dubet & Duru-Bellat, 2015;Duru-Bellat et al, 2018;OCDE, 2019;Vallet, 2017).…”
Section: Iv) Conclusion Et Perspectivesunclassified
“…En effet, on sait à présent qu'un gradient socio-économique s'installe dès le plus jeune âge dans toutes les sphères du développement du jeune enfant, et notamment dans les capacités cognitives (Berger et al, 2020;Grobon, 2018;NELP, 2009;Smithers et al, 2018). Ces inégalités de développement entraînent très vite des effets cumulatifs dans les retards d'apprentissages qui peuvent à leur tour limiter les opportunités éducatives et la mobilité sociale en l'absence d'interventions adaptées (Barone et al, 2021;Duru-Bellat et al, 2018;Lahire & Bertrand, 2019;Vallet, 2017). Face à ces constats, afin de réduire efficacement les inégalités, l'une des priorités des politiques publiques est donc de trouver des leviers qui pourraient agir sur leur origine, c'est-à-dire dans la petite enfance.…”
Section: Introductionunclassified